Analisis Rantai Pasok Komoditi Bawang Merah Di Pasar Bersehati Kota Manado - Nabila, Afifa; Baroleh, Jenny; Rumangit, Grace Adonia Josefina (Sam Ratulangi University, 2023)
This study aims to analyze the shallot commodity supply chain at the Bersehati Market in Manado City and to determine the marketing efficiency of the shallot commodity supply chain at the Bersehati Market in Manado City. This research was conducted at the Bersehati Market from January 2023 to March 2023. The sample determination in this study used a purposive sampling method. There were 24 research respondents consisting of 4 wholesalers and 20 retailers. This study uses two types of data, namely primary and secondary data. The data analysis used is quantitative descriptive analysis. The results of the study show that the shallot supply chain at Bersehati Market is based on product flow moving from upstream to downstream starting from farmers, collectors, retailers, wholesalers, retailers and consumers. Financial flows move from downstream to upstream starting from consumers, retailers, wholesalers, collectors and farmers with cash payment systems and bank transfers. The flow of information moves from two directions, information is provided regarding the quality, quantity and price of shallots. The marketing efficiency level of shallots at the Bersehati Market is below 33%. This shows that the shallot supply chain at the Bersehati Market in Manado City has been efficient.